SME contributions for diversification and stability in emerging economies – An empirical study of the SME segment in the Qatar economy - Fernandez, Raj; Ali, Dr Shaukat (The journal of contemporary issues in business and government, 2015)
Diversity has a significant influence on economic output, productivity and growth’ (Marra, Carlei & Crociata 2011). A healthy SME sector is vital to the sustainability and growth of an economy, especially in emerging economies as their business composition is mostly dominated by the SME segment. Similar to most economies in the MENA (Middle Eastern and North Africa) region, Qatar’s economy predominantly depends on the gas and oil industry. This paper discusses the challenges faced by SME’s in Qatar and financial institutions’ and the perception of barriers to SMEs in terms of lending and support. The research involved a qualitative and quantitative analysis of the research data. A preliminary assessment of secondary data was conducted to establish the current standing of Qatar’s SMEs and compare this with similar emerging markets and more developed economies. Data was obtained for the qualitative element of the study through structured interviews with banking professionals and questionnaires completed by SME entrepreneurs in Qatar. The paper also revealed that there are differences between stakeholders of the SME segment which present further challenges and recommends solutions to these challenges.